Extraction kinetics of ruthenium in the mixture of tri-n-butyl phosphate and n-dodecane. (January 2016) - Ramakrishna Reddy, S.; Trikha, Rahul; Murali, Remya; Augustine, Elizabeth; Desigan, N.; Pandey, Niranjan K.; Mallika, C.; Mudali, U. Kamachi; Joshi, J.B.
Abstract: The extraction kinetics of ruthenium in the mixture of tri- n -butyl phosphate and n -dodecane has been investigated experimentally, using a constant interfacial area stirred cell. Effect of stirring speed, temperature, specific interfacial area and concentrations of reactant and nitric acid on the extraction rate of ruthenium were studied to identify the reaction location, extraction reaction regime and also to determine the intrinsic rate constant of the reaction and mass transfer coefficients. A systematic approach was adopted for the determination of rate parameters. Based on experimental results it is concluded that the reaction with the extractant takes place at interface and the overall rate is controlled by both the intrinsic kinetics and the mass transfer of the species involved. Graphical abstract: Highlights: A comprehensive model is developed to describe the extraction kinetics of Ru in TBP. Rate–constant and mass transfer coefficient determined experimentally and their correlation derived. Extraction of Ru into TBP-dodecane mixture is an interfacial reaction. Overall extraction kinetics is both kinetic and diffusion controlled. Short residence time contactor may improve decontamination of U and Pu from Ru.